A retrospective cohort review of BMI on SI joint fusion outcomes: examining the evidence to improve insurance guidelines - Beckmann, Michael; Odland, Kari; Polly, David W. (European spine journal, 2025)
Purpose The demand for SIJ fusion among obese patients has grown substantially. However, the clinical relevance of obesity in the context of SI joint fusion has not been well investigated specifically, whether there is a BMI cutoff above which the benefit-risk ratio is low. Methods Adult patients ≥ 21 years of age who underwent minimally invasive SIJ fusion between 2020 and 2023. Participants were classified using the National Institutes for Health body mass index (BMI). Patients with a BMI of 30 to 39 with no significant comorbidity are considered obese, patients with a BMI of 35 to 39 with a significant comorbidity or a BMI of 40 or greater are considered morbidly obese. All subjects completed the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) at baseline and 12 months. One-way analysis of variance was used to examine the impact of BMI category on score changes. Results Overall, mean VAS improved at 12 months by 2.5 points ( p < .006). Over the 12-month follow-up period, BMI category did not impact mean improvement in VAS (ANOVA p = .08). Mean ODI at 12 months improved by 23.2 points ( p < .001). BMI category did impact mean improvement in ODI (ANOVA p = .03). Conclusion This study demonstrates similar benefits across all BMI categories. This data suggests that obese patients do benefit from minimally invasive SIJ fusion, specifically the 35–40 BMI cohort of patients, and should not be denied this procedure based on arbitrary healthcare organizations BMI criteria.